2015
DOI: 10.18632/oncotarget.6566
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput qRT-PCR validation of blood microRNAs in non-small cell lung cancer

Abstract: Validation of biomarkers is essential to advance the translational process to clinical application. Although there exists an increasing number of reports on small non-coding RNAs (microRNAs) as minimally-invasive markers from blood, serum or plasma, just a limited number is verified in follow-up studies. We used qRT-PCR to evaluate a known miRNA signature measured from blood that allowed for separation between patients with non-small cell lung cancer (NSCLC), COPD and healthy controls.From the data of our prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 22 publications
1
61
0
Order By: Relevance
“…The study on Alzheimer's disease included, for example, 103 patients with Alzheimer's disease, 77 unaffected controls, and 110 disease controls (e.g., mild cognitive impairment). For lung cancer patients, we successfully validated a signature that was originally generated by microarrays [68] by using high-throughput RT-qPCR [72]. However, there are also reports of failed attempts to reproduce miRNA signatures.…”
Section: Mirna Signaturesmentioning
confidence: 99%
“…The study on Alzheimer's disease included, for example, 103 patients with Alzheimer's disease, 77 unaffected controls, and 110 disease controls (e.g., mild cognitive impairment). For lung cancer patients, we successfully validated a signature that was originally generated by microarrays [68] by using high-throughput RT-qPCR [72]. However, there are also reports of failed attempts to reproduce miRNA signatures.…”
Section: Mirna Signaturesmentioning
confidence: 99%
“…In an exploratory phase I/II biomarker study, Hennessey et al identified a miRNA pair (miRNA-15b and miRNA-27b) able to distinguish between NSCLC (n 5 55) and cancer-free patients (n 5 75), with a specificity of 84% (95% CI, 0.73-0.91) and sensitivity of 100% (95% CI,0.93-1.0) [42]. Leidinger et al used qRT-PCR analysis to identify a set of five markers able to separate lung cancer patients (n 5 74) from healthy controls (n 5 20), with a specificity of 98% (95% CI, 0.95-1.0) and sensitivity of 91% (95% CI, 0.87-0.94) [43]. In addition, they were able to differentiate NSCLC patients (n 5 74) from patients with chronic obstructive pulmonary disease (n 5 26), with a specificity of 81% and sensitivity of 86% using 10 miRNA markers.…”
Section: Diagnosis and Screening Of Lung Cancermentioning
confidence: 99%
“…The data of miRNA profiles in different conditions in this study rely on Agilent's microarray technology, which has shown a high reproducibility and acceptable sensitivity in previous studies. 5 Using microarrays we recently published a Human miRNA Tissue Atlas, which is freely accessible (www.ccb.uni-saarland.de/tissueatlas). 6 In this study we first investigated the influence of degradation on tissue miRNA patterns and then profiled altogether 31 different organs from 2 corpses.…”
Section: Introductionmentioning
confidence: 99%